Managerial capital, occupational choice and inequality in a global economy. (May 2017) - Dinopoulos, Elias; Unel, Bulent
Abstract: This study proposes a simple theory of trade with endogenous firm productivity, occupational choice and income inequality. Individuals with different managerial talent choose to become entrepreneurs or workers. Entrepreneurs enhance firm productivity by investing in managerial capital. The model generates three income classes: low‐income workers facing the prospect of unemployment, middle‐income entrepreneurs managing domestic firms and high‐income entrepreneurs managing global firms. Trade liberalization policies raise unemployment and improve welfare. A reduction in per‐unit trade costs raises top incomes and generates labour‐market polarization. A reduction in fixed exporting costs has an ambiguous effect on top incomes and personal income distribution. Policies reducing labour‐market frictions or the costs of managerial‐capital acquisition create more jobs and improve welfare. The income distributional effects of labour‐market policies depend on which policy is implemented.